BABE : Comparaison des sites de Ronce et Baie de Veys, incidence sur la reproduction et les mortalités : Ecologie côtière, mortalités, croissance, environnement - Physiologie - Immunologie - Soletchnik, Patrick; Le Moine, Olivier; Faury, Nicole; Guilpain, Patrice; Geairon, Philippe; Razet, Daniel; Seugnet, Jean-luc; Robert, Stephane; Ropert, Michel; Simonne, Charlotte; Hugonnet, Virginie; Moal, Jeanne; et al. (Présentation Séminaire MOREST, 13-15 novembre 2002, Brest, 2002)
Four laboratories are involved in this multidisciplinary study: the Conchological Laboratory of Normandie (LCN), the Invertebrates Physiology Laboratory (LPI), the Université Bretagne Occidentale (LEMAR IHP) and the Conchological Laboratory of Poitou-Charentes (LCPC). The part of the study which is presented here (thematics "Coastal ecology") was produced in collaboration with the LCN. The data on the Bay of Veys was collected by Michel Ropert. This study aims at observing the "sites" effect on mortality and on the general biology of the animal, as well as measuring some environmental elements (e.g. water temperature, etc.). The geographical sites are Gefosse in the Bay of Veys (East Cotentin) and the Ronce bank in the south of the Marennes Oléron Bay. The biological material is a pool XS3 (G1) of oysters kept in Bouin in 2001 and free from any mortality at the beginning of the experiment in March 2002. The total mortality rate is 16-17 % in 6 culture months on both oyster culture sites. Maximum mortality appears at the end of June in the Marennes Oléron Bay and at the end of August in the Bay of Veys. No "site" effect appears in the framework of this study, with this stock. The drop of the Walne and Mann condition index (dry weight/ shell weight x 1000) shows that the egg-laying happened during the second week of August in the Marennes Oléron Bay (drop of the index from 60 to 20) and later, during the second half of August, in the Bay of Vey (drop of the index from 120 to 50). In the Marennes Oléron Bay, the water temperature rises beyond 19°C between June 16th and June 23rd. The daily mortality rate rises above 0.5% between June 23rd and June 29th. In the Bay of Veys, the temperature nearly reaches 19°C on July 30th. No mortality happens during the following days. Between August 15th and August 27th, the temperature is above 19°C. Mortality rises above 0.4% between August 26th and September 10th. Quatre laboratoires sont impliqués dans cette étude pluridisciplinaire : le Laboratoire Conchylicole de Normandie ...